The Effect of Hand Grip and Pull Up Exercises on Service Skills for Volleyball Extracurricular at SMK Negeri 3 Seluma - Made Anggara Dwi Ardika; Mesterjon Mesterjon; Mariska Febrianti (Sinar Sport Journal, 2021)
This study aims to: determine the effect of hand grip and pull up exercises on service skills on volleyball extracurricular at SMK Negeri 3 Seluma. The approach method used in this research is descriptive method with quantitative research type, namely research based on calculations in the form of numbers using statistical calculations. The population in this study were 15 students. The sampling technique in this study used a side total technique, namely the sampling technique taking all members of the population as samples or respondents, namely 15 students. The data collection used in this study was by using a service test on volleyball. The data analysis technique used in this research is the t-test analysis technique. From the results of the analysis using the t-test, the value of t-count is = 6.410. When compared with the value of t table with a significance of 5% at n = 15, found a value of 2.145. From this value, it is known that t count is greater than t table (6,410 > 2,145), then Ha is accepted and Ho is rejected, meaning that in this study there is an effect of hand grip and pull up exercises on service skills for volleyball extracurricular at SMK Negeri 3 Seluma.